Electrolyte gated oxide pseudodiode for inhibitory synapse applications - Fu, Yang Ming (2019)
Recently, synaptic electronics are attracting increasing attention in neuromorphic engineering. Here, inhibitory synapses are proposed based on nanogranular phosphorous silicate glass gated indium tin oxide transistors operated in pseudodiode mode. Activity dependent inhibitory synaptic behaviors are mimicked on the proposed pseudodiode, including paired pulse depression and depression adaptation behaviors. Interestingly, the proposed inhibitory synapse demonstrates low power dissipation as low as ≈16 fJ for triggering a postsynaptic current with high signal‐to‐noise ratio of ≈2.2. Moreover, the inhibitory synapse demonstrates zero resting power dissipation. The proposed pseudodiode‐based inhibitory artificial synapses may find potential applications in neuromorphic platforms.